Windows Azure data storage - Johnson, Bruce (Computing consultant) (Programmer to programmer., 2014)
This book provides the tools needed to provide storage that is accessible both from Windows Azure applications and any application connected to the Internet. It starts with an overview of the fundamental concepts, and then covers configuring, scenario mapping, security, backup, recovery, and maintenance of the various data storage options.